Prehospital pediatric King LT-D use: a pilot study - Ritter, Seth C; Guyette, Francis X (Prehospital emergency care, 2011)
To determine whether prehospital providers can successfully place a pediatric King laryngeal tube (LT-D) and ventilate a Laerdal SimBaby pediatric simulator during a respiratory arrest simulation. We studied the ability of 45 paramedics and flight nurses to place the pediatric King LT-D in a SimBaby manikin. For the purposes of this study, paramedics and flight nurses were considered equivalent, because in this air medical system they have the same scope of practice in regard to airway skills. Because the participants had previous training and field experience with the adult King LT-D, we limited pediatric King LT-D training to our standard adult training plus selecting the correct size and inflation volumes for the device. Outcomes included rate of successful pediatric King LT-D placement, number of attempts to correctly place the tube, and time to first adequate ventilation. The subjects were evaluated on airway management using an 11-point skill test. A score of 8 or greater (≥ 73%) was considered passing. The subjects indicated their perceptions and preferences for the pediatric King LT-D using a five-point Likert scale. Data were analyzed using descriptive statistics. Crew members successfully placed the pediatric King LT-D 95.5% (43/45) of the time. The median number of attempts was one. Four subjects required a second attempt; two of these subjects failed at placement. Mean time to placement was 34 seconds (95% confidence interval [CI]: 26.4-67.3 sec). Ninety percent of the participants (40/45) successfully completed the skill test, with a mean score of 78.2% (95% CI: 73.6-82.7). The subjects strongly agreed that their previous training on the adult King LT-D and using it in the field had adequately prepared them to use the pediatric King LT-D. The subjects agreed that the pediatric King LT-D was easier to place than a pediatric endotracheal tube; they strongly agreed that they would use the pediatric King LT-D as an alternative airway. The participants disagreed that they would prefer the pediatric King LT-D as a primary means of securing pediatric airways. The pediatric King LT-D was quickly and reliably placed. Providers perceived the pediatric King LT-D to be easier to use than pediatric endotracheal intubation in this setting.